The Influence of Organizational Culture, Work Discipline, and Work Environment on Employee Performance: A Study at PT Bank Mandiri (Persero) Tbk, Palembang A. Rivai Branch (International Journal of Environmental Sciences, 2025)
This study aims to analyze the influence of organizational culture, work discipline, and work environment on employee performance at PT Bank Mandiri (Persero) Tbk, Palembang A. Rivai Branch. A quantitative approach was used with a survey method by distributing questionnaires to 62 respondents. Multiple linear regression analysis was employed to examine both the simultaneous and partial effects of the independent variables on employee performance.The results showed that organizational culture, work discipline, and work environment had a positive and significant influence on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 81.7% indicates that these three variables collectively explain the variability in employee performance. These findings highlight the importance of organizational culture alignment, enforcement of work discipline, and the creation of a conducive work environment in improving employee performance in the banking sector.